"International Hegemony in Global Supply Chains: Specialization, Risk, and Geopolitical Transformations - Tabark Hamoodi Shakir; Saif Nussrat tawfeeq (Tikrit Journal For Political Science, 2025)
This research explores the evolution of global supply chains and their transformation into strategic tools for major industrial powers. By analyzing the roles countries play within these chains, it sheds light on the structural gap between hubs of innovation and peripheral manufacturing zones. The study highlights the vulnerabilities of global supply chains amid rising geopolitical tensions, pandemics, and technological rivalries. It concludes that global economic stability now hinges not only on market performance, but on the resilience and strategic management of cross-border supply systems.